EFFECT OF STRATEGIC DIRECTION ON STRATEGY IMPLEMENTATION AT THE SELECTED MULTINATIONAL AGROCHEMICAL COMPANIES IN KENYA - Waithaka, Dr. Paul; Makori, Nathan Nyarunda (European Journal of Business and Strategic Management, 2019)
Purpose: Agriculture in Kenya attracts several stakeholders including agrochemical companies. Since the return on investment is considerably high, the sector has experienced several new entrants selling and marketing agrochemical products in Kenya since 2010. As a result, large agrochemical companies have developed and adopted several strategies evident from 2014. For survival, these strategies have to be implemented successfully; this normally is contingent on many factors. For a successful implementation of selected strategies in agrochemical companies operating in Kenya, factors impeding and/or favouring the implementation need to be identified. Among the factors shown to enhance successful strategy implementation, is roles played by strategic leaders. This study seeks to determine the effect of strategic direction on strategy implementation at the selected multinational agrochemical companies in Kenya. The theories underpinning this study were top echelon theory, transformational leadership theory and implementation theory. Methodology: This study adopted an explorative research design. The target population was the strategic leaders at the seven multinational agrochemical companies in Kenya adding up to 70 in number. Census was used as the population is small thereby minimising error. A semi-structured questionnaire was used to collect both quantitative and qualitative data. Qualitative data was analysed manually using content analysis method while quantitative data will be analysed using SPSS version 20 software. The influence of the strategic leadership role on strategy implementation was analysed using multiple regression analysis. Data were presented using tables, pie charts and graphs to make them reader-friendly. Results: R square value of 0.799 means that 79.9% of the corresponding variation in strategy implementation at the selected multinational agrochemical companies can be explained or predicted by (Strategic Direction) which indicated that the model fitted the study data. Unique Contribution to Theory, Practice and Policy: Based on the study findings, the study concludes that strategy implementation at the selected multinational agrochemical companies in Kenya can be improved by Strategic Direction. Other studies can seek to assess the influence of leadership styles on organizational performance of agrochemical companies.